Trajetórias do PRONAF em Sergipe : desenvolvimento e mudanças sócio-espaciais - Carvalho, Diana Mendonça de (2016)
The Program for Strengthening Family Agriculture (Pronaf) is now an essential element in promoting processes of socio-spatial changes in the Brazilian rural context. A policy that has spread almost throughout Brazil is increasing as support for the fight against rural poverty. It is a policy directed to small farmers, demarcated by the State as family farmers, aimed at promoting rural development, due to the entreprising and potentiating character of these actors with local economies. The thesis is justified by the government's persistence in maintaining the program that is about to turn 20; the importance that the Pronaf began to show in the financing of family farming; and also the possibility of credit universalization among these farmers. From this perspective, this paper analyzes the changes in the Sergipe countryside, from the implementation of Pronaf. The research is analytical and empirical, valuing qualitative and quantitative aspects that reflect information and knowledge of reality. The theoretical contributions had plural character, adding aspects not only geographical, but in other areas of knowledge. The rationale resumes discussions on rural development, family agriculture and institutionalism as segments integrated into the operation and socio-spatial consequences made possible by Pronaf. At also the sum of the methodological procedures established to carry out this work, the score is: conducting interviews with institutional entities and questionnaires with program beneficiaries through the analysis of three counties, by type, had the largest number of committed contracts in 2012: Capela (mode a); Itabaianinha (mode B); and Carira (common mode). The evaluation of data collected in the field proves that Pronaf is not a determining factor for agricultural production in Sergipe, but it is essential for the promotion of socio-spatial changes in terms of land ownership, productive diversification, integration of elements of technical scientificinformational means, creating marketing networks and consumption of goods and family restructuring. The program continues adding changes in their normative aspects, with subsidized interest rates, coordination with other policies, methodology building for effective policy (Agroamigo), creation of specific credit lines and inserting the farmer's market circuit. However, it is known that even becoming a foundation for improving the quality of life for farmers and promoting rural development, PRONAF must still overcome some bottlenecks, particularly in relation to bureaucratic question and the provision of technical assistance and rural extension. Nevertheless, PRONAF has been a mainstay in promoting economic and spatial changes, considering represent a foundation for many family farmers who were below the poverty line and have no access to credit opportunities in the conventional funding system, breaking, thus, to the exclusion and urging the financial capacity of small production units. In this respect, it can assert that for Sergipe, PRONAF as a social feature policy has been supportive of rural and local development.